Changing scenario of the cut flower industry in central Kerala - an economic analysis. - Lisma Steephan (Department of Agricultural Economics, College of Horticulture, 2011)
Floriculture is fast emerging as a lucrative profession in the world scenario and is a potential money spinner for many countries. In terms of production, floriculture in the world is growing at an average rate of 10 per cent per year. Floriculture is a multi-crore industry in India which contributes 0.6 per cent to global floriculture trade. In 2009-10 the total area under floriculture was estimated to be 1,83,000 hectare with an estimated production of 1021 metric tonnes of loose flowers and about 6667 million numbers of cut flowers. Cut flowers like orchid and anthurium are identified as the most important flowers with commercial potential suitable for Kerala. The present study was done to investigate the economics of cut flower enterprises, marketing channel and marketing efficiency of cut flower trade and to identify the constraints of cut flower industry in Central Kerala. Orchid and anthurium were the major cut flowers included in the study. The study was conducted with a sample of 120 cut flower growers. Percentage analysis, ABC cost concept, Capital productivity analysis and Shepherd’s formula were used to analyze the data. Orchid and anthurium growing units have been studied across three scales of operation, viz., small (less than 500 plants: C-I), medium (500 to 1000 plants: C-II) and large (above 1000 plants: C-III) for a standard of 100 plants in each categories. Anthurium Per unit cost of cultivation of anthurium showed increasing pattern towards smaller groups. According to ABC cost concept cost of cultivation for five years for C-1, C-11 and C-111was estimated to be Rs. 15,164, Rs.11,486 and Rs.9,963 respectively. The establishment cost was found out to be Rs.13,116 (C-1), Rs.12,008 (C-11) and Rs.11,330 (C-111). Recurring cost ranged from Rs.2,500 in C-111 to Rs.6,315 in C-111. The total return realized over crop life varied from Rs.32,790 to Rs.41,152 in different scales of operation. The estimated project worth parameters were well above acceptance level in C-11 and C-111. Orchid According to ABC cost concept cost of cultivation for five years for C-1, C- 11 and C-111 was estimated to be Rs. 15,932, Rs.13,017 and Rs.11,199 respectively. The establishment cost was found out to be Rs.13,397 (C-1), Rs.12,607 (C-11) and Rs.13,092 (C-111). Recurring cost was Rs.2,450 in C-111, Rs.3,835 in C-11 and Rs.6,025 in C-1. Per unit cost of cultivation was found to be decreasing as the scale of operation increases. The total return realized over the economic life of the crop was found to Rs.27,640 in C-1, Rs.30,461 in C-11 and Rs.35,474 in C-111.Higher returns were realized from larger units. The estimated project worth parameters were well above acceptance level in all the categories. Capital productivity analysis of orchid and anthurium showed that larger units were seen comparatively more efficient and profitable than smaller ones. In anthurium cultivation only family labour was utilized for all operations in three scales of operation. But in case of orchid, hired labour was employed for potting and planting in C-111. Marketing channels and efficiency Six marketing channels were identified for anthurium. The direct channel i.e. Producer Consumer was found to be more efficient. Out of the three marketing channels identified for orchid, Producer Local florists’ Consumer was identified as the most efficient channel. Constraints in cut flower trade The most serious problem faced by orchid and anthurium growers, especially smaller sized units, was low market price for their products. Irregular markets followed by delay in getting sale proceeds were identified as the other major constraints faced by the growers. Short supply of flowers, lack of government support, lack of storage facilities etc. were the major problems faced by cut flower traders. Effective production planning and marketing management were identified as the key factors for the development of the sector.